Exploring Figurative Language used in One ok Rock song’s lyrics - Turnip, Trisnawati; Manik, Sondang; Sihete, Jubil Ezer (English Lecturers and Teachers Association (ELTA), 2025)
The aims of the study is to find out the kinds of figurative language used by the One Ok Rock in their 10 songs. The source of this research data is taken from the One ok Rock album You-tube channel and this research only focuses on Figurative Language used by the One ok Rock. The writer uses a qualitative descriptive method to explain meaning of figurative language by using the theory Kennedy & Gioia (2000) the result of this research were the discovery of 3 types of language styles according the theory of Kennedy & Gioia (2000), comparative figurative language, contradictive figurative language, and correlative figurative language. From the writer research it is known that the types of figurative language writer found 93 figurative language used in One ok Rock in the 10 songs, namely personification 37%, simile 5%, metaphor 35%, hyperbole 11%, paradox 1%, irony 1%, symbolism 4%, allusion 1%, ellipsis 1%. , it means that personification and metaphor is the biggest number used in those albums, as a song that telling massage in figurative language : using personification and metaphor saying a comparative in figurative language ,while in contradictive figurative language writer found 11 % The metaphorical concept contained in this sentence can be interpreted as being too negative emotionally, such as